Mapping early fate determination in Lgr5+ crypt stem cells using a novel Ki67‐RFP allele. (4th August 2014) - Basak, Onur; van de Born, Maaike; Korving, Jeroen; Beumer, Joep; van der Elst, Stefan; van Es, Johan H; Clevers, Hans
Abstract Cycling Lgr5+ stem cells fuel the rapid turnover of the adult intestinal epithelium. The existence of quiescent Lgr5+ cells has been reported, while an alternative quiescent stem cell population is believed to reside at crypt position +4. Here, we generated a novel Ki67RFP knock‐in allele that identifies dividing cells. Using Lgr5‐GFP;Ki67RFP mice, we isolated crypt stem and progenitor cells with distinct Wnt signaling levels and cell cycle features and generated their molecular signature using microarrays. Stem cell potential of these populations was further characterized using the intestinal organoid culture. We found that Lgr5high stem cells are continuously in cell cycle, while a fraction of Lgr5low progenitors that reside predominantly at +4 position exit the cell cycle. Unlike fast dividing CBCs, Lgr5low Ki67− cells have lost their ability to initiate organoid cultures, are enriched in secretory differentiation factors, and resemble the Dll1 secretory precursors and the label‐retaining cells of Winton and colleagues. Our findings support the cycling stem cell hypothesis and highlight the cell cycle heterogeneity of early progenitors during lineage commitment.